A Critical Appraisal of Daivavyapashraya Chikitsa w.s.r to Mantra and Homa in Adhyatmika Vyadhis (AYUSHDHARA, 2024)
This study aimed to explore the importance of Mantra and Homa (Yagya) in the management of Adhyatmika vyadhis (psychosomatic disorders). Ayurveda and other Vedic classics have explained three types of diseases such as Adhyatmika (Karmaja, Kulaja, Sahaja, Prakritibhava), Adhibhautika, and Adhidaivika. The Chikitsa such as Daivavyapashraya, Yuktivyapashraya, and Satvavajaya are Trividha Chikitsa mentioned in Ayurveda and Daivavyapashraya Chikitsa are useful for enhancing the spiritual power of the patient. It includes 14 sub-segments among them Mantra and Homa have been selected for this study. Importance of Adhyatma dravya guna sangraha and Sadhvruta following - Japa, Mantra, and Homa are clearly mentioned in Ayurveda. The Bhagavad Gita explanation has been given about Tapatraya (Adhyatmika, Adhidaivika and Adhibautika). Vishnu Sahasranama mantra, Shiva Shiva Sthuti, Rakshogna mantra, Putrayasti yagya and Nirgundi patra Dupa followed by Mantra have been prescribed for Abhishapaja Jwara, Kushta, Vandyatwa and Visham jwara respectively. The effects of Yagya therapy on diabetes, stress, and anxiety have been scientifically proven. The mechanism of Yagya has been explained as follows; inhalation of Yagya vayu (medicinal smoke) is supposed to give immunity and strength, while exhaled breath provides removal of toxins out of the body. Changing the sound pattern while chanting the mantras can change the energy of the entire body and it balances the Tridosha. Hence it can be concluded that Homa and Mantra must have a significant effect on the management of Adhyatmika Vyadhis.